The awareness level of employees towards Enterprise Wide Risk Management (EWRM) in Tenaga Nasional Berhad (TNB) Petaling Jaya / Maisara Abdul Rahim - Abdul Rahim, Maisara (Faculty of Business and Management, 2011)
This research study is about The awareness level of employees toward Enterprise Wide Risk Management (EWRM) in Tenaga Nasional Berhad (TNB) Petaling Jaya. The study was conducted with three objectives which are to determine the level of employee awareness towards Enterprise Wide Risk Management at TNB Petaling Jaya, to identify the significant relationship between employee awareness and the independent variables and to identify the most influence factors for associate the dependent variable. The respondents of this study were the employees of Tenaga Nasional Berhad (TNB) and 40 questionnaires had been distributed. In this study, the descriptive statistics had been used to interpret the data such as reliability testing, frequency tables and correlation. From the finding, respondents are aware with the Enterprise Wide Risk Management. The result shows the relationship between the level of awareness and promotions are positive. Besides that, Research also comes out with some recommendation in order to enhance the importance of EWRM among employees